Pencegahan Kenakalan Dalam Kalangan Remaja Yang Keciciran Daripada Persekolahan Di Cimahi Selatan, Provinsi Jawa Barat, Indonesia - Susilawati, Susilawati (2013)
This research was carried out to support the prevention efforts of delinquency in more comprehensive manner especially to the juveniles at risk. The objectives of this study are: (i) to identify the pattern of the delinquency of dropout juvenile , (ii) to explain the factors of the delinquency influence, and (iii) to examine the effectiveness of delinquency prevention model. This study used quantitative and qualitative approaches. Quantitative approach for the first and second objectives used the survey method, whereas for the third objective was conducted using the experimental method. Therefore, data collection has been carried out using a questionnaire to 62 selected school dropout juveniles by the area random sampling. A qualitative approach was conducted using in-depth interviews and focus group discussions involving 57 participants (including school dropout juveniles, parents, organization leaders and local governments, Cimahi government officials), and it is equipped by document review. The findings of this study showed that 94% of school dropout juveniles were involved in several types of minor delinquency and 19.35% involved in the high to very high level of delinquency. The test results of the path analysis showed that the delinquency was influenced by self-esteem (18.10%), social skills (16.70%), support from parents (14.10%), and social bonding with their negative peer group (31.00%).The contributions of the above factors are 79.90%.